The Implementation of Student Management in Discipline Guidance at Modern Islamic Boarding Schools Gontor - Taufik Rizki Sista; Albab Sodiqin (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
The objective of this study was to determine the pattern of student discipline development at Gontor campus 2, determine the implementation of student management in the development of student discipline at Gontor campus 2, and determine the supporting and inhibiting factors in implementation of student management in student discipline development at Gontor campus 2. The research method used by the researcher is a qualitative research method with a phenomenological approach where the discipline enforcement system is a unique phenomenon that was pointed out in this study. The data analysis technique utilized is Milles and Huberman triangulation in data reduction, display, and verification. The results of this study are (1) the pattern of student discipline development at Gontor campus 2 is based on the pesantren system with 24-hour parenting patterns with security discipline settings, class entry discipline, and language discipline. (2) The implementation of student management at Gontor is carried out by the guidance staff collaborating with KMI staff and the language advisory council. Implement the POACE system to implement the discipline. (3) there are supporting and inhibiting factors in implementing student management in Gontor campus 2. The summarized conclusion describes that the application of student management at Gontor is an effort to maintain the existence of the Pesantren as a moral education institution. Efforts to improve students' morale are performed by applying POACE's performance in the implementation of student management.